How far will we travel? A global distance pattern of international travel from both demand and supply perspectives. Issue 8 (December 2019) - Sun, Ya-Yen; Lin, Pei-Chun
The travel distance of international journeys critically determines our reliance on different transportation modes and the associated carbon intensity. This study quantified the influence of macrolevel determinants to the inbound and outbound average distance per visitor from a panel data of 152 countries using spatial econometric analysis. Results confirmed that national development and transport capacity assisted the spatial expansion of outbound travel, while tourism competitiveness, geographic attributes, and institutional arrangements regarding people's mobility facilitate inbound visits from distant source markets. A high level of heterogeneity was found across five continents where the distance friction effect through geographic barrier, transport accessibility, and the freedom of people's movement exhibited a different level of influences. To manage the spatial expansion of international travels for a sustainable transport future, a strong geopolitical integration system across countries within the region and adjustments to the aviation capacity to disfavor long-haul flights have been proposed.